THE EFFECT OF BALANCED SCORECARD IMPLEMENTATION ON MANAGEMENT PERFORMANCE PT BANK SYARIAH MANDIRI - Fikriani, Alifia (al-Uqud : Journal of Islamic Economics, 2019)
This study is the application of balanced scorecard on performance management of the Bank Syariah Mandiri Branch Bogor. Utilized a quantitative approach,the statistical method used is multiple linear regression. The sampling method was convenience sampling, which were 38 employees of Bank Syariah Mandiri Bogor. The quality test data used in this study using a test of validity, reliability testing, and distribution frequency questionnaire statement. As for testing the test, the test, t-test, and test the coefficient of determination. The results of the SPSS Version 23.0 for the adjusted R Square result were obtained from the SPSS were 89.4% while the remaining 10.6% were influenced by other variables that are not known. The results show that customer perspective, learning and growth perspective variables are positive and significant effect on management performance. While the financial perspective and internal business process have a positive and not significant perspective on management performance in Bank Syariah Mandiri Branch of Bogor.